2018
DOI: 10.1007/s00405-018-4934-3
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy in cutaneous head and neck melanoma

Abstract: As in other sites, SLNB status is a strong prognostic factor with comparable false omission rate and no superior morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
6
13
1
Order By: Relevance
“…However, our study shows that SLNB‐guided regional nodal management of cN0 HNCM is highly efficacious, evidenced by 85.4% regional disease control with 4.9 years of median follow‐up. Additionally, while parotid dissection was historically viewed as technically challenging and potentially dangerous, we demonstrate a low long‐term intraparotid false omission rate of 5.8%, which favorably compares to prior studies and is notably superior to the 6.4% long‐term false omission rate for the entire study cohort …”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, our study shows that SLNB‐guided regional nodal management of cN0 HNCM is highly efficacious, evidenced by 85.4% regional disease control with 4.9 years of median follow‐up. Additionally, while parotid dissection was historically viewed as technically challenging and potentially dangerous, we demonstrate a low long‐term intraparotid false omission rate of 5.8%, which favorably compares to prior studies and is notably superior to the 6.4% long‐term false omission rate for the entire study cohort …”
Section: Discussionsupporting
confidence: 63%
“…We have previously reported only a single case of mild lymphedema following iCLND in this cohort, resolving spontaneously within 4 weeks . Moreover, HNCM was historically viewed as sufficiently unique to evoke intense skepticism prior to SLNB's widespread adoption . Likewise, our study suggests that MSLT‐II's conclusions similarly warrant intense scrutiny before abandoning H&N iCLND, which may increase CN injury frequency and severity .…”
Section: Discussionmentioning
confidence: 72%
“…9,26-29 Since then, studies at other institutions have replicated and confirmed these findings. 9,30-32 We present an updated analysis of Erman and colleagues’ large single-institution HNCM cohort 9 with long-term follow-up, which validates SLNB’s long-term safety, accuracy, and prognostic utility for HNCM. SLN status remains highly prognostic for OS, MSS, RFS, and regional RFS.…”
Section: Discussionmentioning
confidence: 62%
“…18 These factors included tumor thickness <2 mm and absence of ulceration. 17,19 Therefore, we performed a subgroup analysis in patients under the age of 60, with non-ulcerated tumors, and Breslow thickness <2 mm. No statistically significant OS difference was found between the SLNB only and the SLNB + CLND groups in this subanalysis, as shown in Figure 3 (87.4% vs 80.3%; P = .47).…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…[10][11][12][13] Dedicated CHNM studies have demonstrated that SLNB is a safe and reliable technique, [14][15][16] and that SLNB status is a strong prognostic factor. 17 The therapeutic role of SLNB and the survival benefit of CLND, however, is less defined in CHNM.…”
Section: Introductionmentioning
confidence: 99%